The Globalization of Knowledge in History - Jürgen Renn (ed.) (Studies 1: Max Planck Research Library in the History and Development of Knowledge, 2012)
Today scientific, technological and cultural knowledge is shared worldwide. The extent to which globalized knowledge also existed in the past is an open question and, moreover, a question that is important for understanding present processes of globalization. This book, the first volume of the series "Studies" of the "Max Planck Research Library for the History and Development of Knowledge," the result of an interdisciplinary cooperation launched in 2007 by a Dahlem Conference, offers surprising answers to this question. Long-distance and intercontinental connections with an attendant spread of knowledge are as old as Homo sapiens themselves. Since its inception, the globalization of knowledge has been a process with its own dynamics, interfering significantly with other processes of intercultural transmission. The four parts of this volume address historical phases in which the production, transmission and transformation of knowledge were crucial for advancing these processes. Part 1 investigates a series of processes in the very early phases of globalization, from the transmission of practical knowledge to the emergence of science. Part 2 explores how knowledge was disseminated as a consequence of the spread of power and belief structures. Part 3 deals with the encounters between culturally specific knowledge and globalized knowledge. Part 4 is dedicated to the globalization of modern science and to the great challenges, such as energy supply and climate change, that humanity faces when dealing with knowledge today The 97th Dahlem Workshop: The present volume is based on the 97th Dahlem Workshop on Globalization of Knowledge and its Consequences, Berlin, 18-23 November 2007, coordinated by Katharina Ochse. Participants: Ian Baldwin, Angelo Baracca, Fabio Bevilacqua, Maria Emilia Beyer, Hans-Peter Blossfeld, Gianluca Bocchi, István M. Bodnár, Jens Erland Braarvig, Chiara Brambilla, Eva Cancik-Kirschbaum, Jacob Dahl, Peter Damerow, Hansjörg Dilger, Kostas Gavroglu, Matteo Gerlini, Denise Gimpel, Gerd Graßhoff, Hans Falk Hoffmann, Dirk Hofäcker, Jarita C. Holbrook, Malcolm D. Hyman, Birgit Krawietz, Manfred Krebernik, Joachim Kurtz, Manolis Patiniotis, Albert Presas I Puig, Daniel T. Potts, Dhruv Raina, Jürgen Renn, Richard Rottenburg, Dagmar Schäfer, Matthias Schemmel, Mark Schiefsky, Meredith Schuman, Gebhard J. Selz, Martina Siebert, Circe Mary Silva da Silva, Ana Simões, Tzveta Sofronieva, Saran Solongo, Karin Tybjerg, Hans Ulrich Vogel, Milena Wazeck, Gerhard Wolf, Harriet T. Zurndorfer